2014
DOI: 10.1530/erc-13-0112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mTOR pathway in human normal adrenal and adrenocortical tumors

Abstract: The mTOR pathway has recently been suggested as a new potential target for therapy in adrenocortical carcinomas (ACCs). The aim of the current study is to describe the expression of the mTOR pathway in normal adrenals (NAs) and pathological adrenals and to explore whether there are correlation between the expression of these proteins and the in vitro response to sirolimus. For this purpose, the MTOR, S6K1 (RPS6KB1), and 4EBP1 (EIF4EBP1) mRNA expression were evaluated in ten NAs, ten adrenal hyperplasias (AHs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
2
26
1
Order By: Relevance
“…Presently, there is no evidence that clearly supports a key role of this pathway in the pathogenesis of ACCs. This is supported by the finding that adrenocortical adenomas have higher mRNA expression of p-mTOR than ACCs [13]. Currently, there is no clear rationale behind the use of mTOR inhibitors as a targeted therapy in ACCs.…”
Section: Discussionmentioning
confidence: 94%
“…Presently, there is no evidence that clearly supports a key role of this pathway in the pathogenesis of ACCs. This is supported by the finding that adrenocortical adenomas have higher mRNA expression of p-mTOR than ACCs [13]. Currently, there is no clear rationale behind the use of mTOR inhibitors as a targeted therapy in ACCs.…”
Section: Discussionmentioning
confidence: 94%
“…The role of the mammalian target of rapamycin (mTOR), a downstream effector of IGF2, has been investigated in adrenal tumors by several studies, and mTOR appeared to be a potential therapeutic target in a subset of patients with ACC (Table 5; De Martino et al 2014). Doghman et al (2010) reported for the first time involvement of miRNAs in regulation of mTOR signaling in childhood adrenocortical tumors.…”
Section: Future Directions and Pathway Driven Therapiesmentioning
confidence: 99%
“…Genetic studies have identified alterations in the FGF-R cascade (Laurell et al 2009), and overexpression of VEGF-R, PDGF-R, EGF-R, and the FGF-R signalling pathways (Xu et al 2011, Wang et al 2012. Preclinical studies support the idea that mTOR inhibitors can upregulate Akt phosphorylation in ACCs (Liu et al 2009, De Martino et al 2014.…”
Section: Molecular Profilementioning
confidence: 82%